Migranti, categorie normative ed esternalizzazione delle frontiere - Paleologo, Fulvio Vassallo (SocietàMutamentoPolitica, 2020)
European governments of different political views, which have closed the channel of legal entry for work, have long believed that the removal and anticipation of border controls in transit countries, as well as confinement or detention of migrants deemed “illegal”, can reduce irregular entry into the territory of the State, and constitute a brake on the submission of applications for international protection, which could not be refused otherwise if people arrived at a land, air or sea border of a State that has acceded to the 1951 Geneva Convention on Refugees. According to the principle of non-refoulement enshrined in the Geneva Convention (Article 33), in fact, no one may be refused entry at the border without having access to a fair and effective procedure to determine his or her status and protection needs. It is therefore possible to identify a procedural “minimum content” of the right of asylum, which, even before imposing on States specific positive obligations regarding the granting of the benefit, does not allow them behaviours that restrict the freedom of access to procedures, and therefore to the territory of the State, unless participation in the Geneva Refugee Convention is rendered meaningless. Agreements between States, as a result of the processes of externalization of borders, cannot legitimise, in the name of a misunderstood national sovereignty, indiscriminate refoulement measures or “closure of ports”.